Unrecognised adrenergic symptoms and the delayed diagnosis of urinary bladder paraganglioma - Dragović, Tamara; Marinković, Dejan; Kuzmić-Janković, Snežana; Milović, Novak; Kovačević, Božidar; Hajduković, Zoran (Vojnosanitetski pregled, 2015)
Introduction. Paraganglioma is a rare neuroendocrine neoplasm that may arise from the extra-adrenal autonomic paraganglia. Urinary bladder paraganglioma is typically presented as repeated episodes of palpitations, headache or blood pressure rise immediately after micturition. Management of these tumors includes radical surgical treatment with preoperative antihypertensive preparation, and a life-long follow-up. Case report. We presented a middle-age female patient with functional urinary bladder paraganglioma, with a 3-year history of repeated episodes of abdominal pain, dysuria and hematuria. After obtaining more precise anamnestic data, the patient reported occasional simultaneous presence of mild adrenergic symptoms, that did not cause any particular attention at first. Morphological and biohumoral examinations suggested paraganglioma of the urinary bladder. Open partial cystectomy was performed, detecting a submucosal mass, while immunohistochemical analysis confirmed the presence of chromaffin tissue. Clinical manifestations, diagnostic approach, management and histopathological findings of urinary bladder paraganglioma are discussed. Conclusion. Since the prognosis with localized paraganglioma is good, we underlined the importance of a well-timed, accurate and detailed medical history in all the patients with even mild, inexplicable micturition-provoked adrenergic symptomatology.